2021
DOI: 10.3390/coatings11040424
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Electromagnetic Shielding Composites Based on Graphene-Nanosheets-Loaded Nonwoven Fabric

Abstract: A fabric-like electromagnetic (EM) shielding composite based on nonwoven was fabricated using a coating method with a mixture containing graphene (GE) nanosheets and polyvinylidene fluoride (PVDF) adhesive agent, and then characterized for its mechanical properties, air permeability, EM properties, and morphologies. The GE loading amount and EM shielding effect was improved by applying a double coating process, with, in particular, a 2-sided coating that produced superior air permeability and shielding effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The EMI SE of a composite material is generally considered to be related to its electrical conductivity [ 36 ]. With increased GE content, the GE/cellulose ratio increased, which improved the conductivity of composite films after drying, since GE nanoplates touched one another more often to form a conductive network with better connectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The EMI SE of a composite material is generally considered to be related to its electrical conductivity [ 36 ]. With increased GE content, the GE/cellulose ratio increased, which improved the conductivity of composite films after drying, since GE nanoplates touched one another more often to form a conductive network with better connectivity.…”
Section: Resultsmentioning
confidence: 99%
“…Another typical preparation method of shielding fabrics is loading graphene nanoparticles on freestanding fabric, such as nonwoven fabric, [187,188] carbon texture, [189] cotton fabric, [190] by a controllable coating process. Zhang et al reported a rGO/ MXene sandwich-structured film on a spunlace nonwoven fabric substrate through a soaking-drying-reduction method.…”
Section: Graphene-based Fabricsmentioning
confidence: 99%
“…Another typical preparation method of shielding fabrics is loading graphene nanoparticles on freestanding fabric, such as nonwoven fabric, [ 187,188 ] carbon texture, [ 189 ] cotton fabric, [ 190 ] by a controllable coating process. Zhang et al.…”
Section: Applications Of Graphene‐based Materials For Electromagnetic...mentioning
confidence: 99%
“…EMI can cause not only the operational malfunction of electric devices but can also severely affect human health. The range of electronic devices and components is gradually increasing due to the commercialization of electric vehicles and, therefore, many researchers are developing EMI shielding materials [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%